2010
DOI: 10.3122/jabfm.2010.05.090186
|View full text |Cite
|
Sign up to set email alerts
|

Nasolaryngoscopy in a Family Medicine Clinic: Indications, Findings, and Economics

Abstract: Background: Nasopharyngeal complaints are common among patients who present to primary care. Patients with these complaints are often referred for nasolaryngoscopy evaluation to exclude serious conditions such as laryngeal cancer.Methods: This study is a retrospective case series in which 276 charts of adult outpatients who were referred for nasolaryngoscopy were reviewed. We examined patient demographics, procedure indications and findings, complications, and changes in clinical management.Results: Nasolaryng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Similar findings were seen in study done by Ahmad Nasratet al 6 In contrary, the problems were found to be more common in male (52.2%) in a study done by Muhammad Shafi et al 7 The most common findings in this study were LPRD which was 38.4%. Similar findings was observed in a study done by Wilkins et al 8 (42.5%), but the incidence of the pathology was low in the article published by Ahmad Nasrat et al 6 (11.4% ). GERD have upper airway symptoms without heartburn in 20-60 % of patients.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings were seen in study done by Ahmad Nasratet al 6 In contrary, the problems were found to be more common in male (52.2%) in a study done by Muhammad Shafi et al 7 The most common findings in this study were LPRD which was 38.4%. Similar findings was observed in a study done by Wilkins et al 8 (42.5%), but the incidence of the pathology was low in the article published by Ahmad Nasrat et al 6 (11.4% ). GERD have upper airway symptoms without heartburn in 20-60 % of patients.…”
Section: Discussionsupporting
confidence: 89%
“…Although nasolaryngoscopy has been evaluated in family medicine clinics, issues of diagnostic accuracy for family medicine physicians vs otolaryngologists have not been addressed. 22 Furthermore, with only 7% of family medicine physicians performing laryngoscopy, another onethird having no training, and 50% no interest in performing this procedure, laryngoscopy by an otolaryngologist is paramount for laryngeal/voice disorder patients. 23 Although our study was unable to address the appropriateness of treatment or progression of disease before otolaryngology evaluation, both issues could have affected the costs involved in evaluating and managing patients with laryngeal/voice disorders.…”
Section: E15mentioning
confidence: 99%
“…A telemedicine-based nasopharyngolaryngoscopy (tele-NPL) system has proven its utility in a variety of situations, such as for consultations in family medicine and other primary care clinics, 9 as well as for resident teaching and educational purposes during inpatient consultations. 7,8 To date, there have been no published studies validating the diagnostic accuracy of flexible fiber-optic NPL recordings.…”
Section: Introductionmentioning
confidence: 99%